NEMS generated electromechanical frequency combs - Sasan Rahmanian; Hamza Mouharrar; Rana Abdelrahman; Masoud Akbari; Yasser S. Shama; Kevin Musselman; David Muñoz-Rojas; Skandar Basrour; Eihab Abdel Rahman (Microsystems & Nanoengineering)
Abstract This paper presents a novel technique for low-power generation of frequency combs (FC) over a wide frequency range. It leverages modal interactions between electrical and mechanical resonators in electrostatic NEMS operating in air to provide a simple architecture for FC generators. A biased voltage signal drives the electrical resonator at resonance which is set to match an integer submultiple of twice the mechanical resonator’s resonance. Experimental results demonstrate that the NEMS displacement exhibit more than 150 equidistant peaks in the case of a 2:1 modal interaction and more than 60 equidistant peaks in the case of a 1:1 modal interaction. In both cases, the Free Spectral Range (FSR) was equal to the mechanical resonance frequency. Comparison between the FCs generated by the 2:1 and 1:1 modal interactions demonstrate the superiority of the former in terms of bandwidth and stability. The superior phase coherence of the FC generated via the 2:1 modal interaction was demonstrated via time-domain analysis. Our technique has the flexibility to generate multiple frequency combs and to fine-tune their FSR depending on the number of mechanical modes accessible to and the order of the activated modal interaction. It can be integrated into portable devices and is well aligned with modern miniaturization technology.